The transition from in-person to online supervision: Does the interaction between doctoral advisors and candidates change?. Issue 6 (2nd November 2021) - Torka, Marc
ABSTRACT: When the coronavirus pandemic hit, most doctoral supervision moved online around the globe. Virtual meetings using videoconferencing technology (VCT) suddenly replaced in person encounters raising the question of whether supervisory interaction has been altered due to changing delivery modes. This article applies a practice-theoretical approach to explore how doctoral advisors and candidates interact in the virtual space and how they experienced the transition to online supervision. Drawing on 11 recorded Zoom meetings and 35 interviews with doctoral advisors and candidates in the social sciences and physics, the study has found that field-specific supervision models fit VCT environments differently. The findings indicate that team-based supervision is more difficult to sustain online than one-on-one supervision where advisors and candidates change little in their usual interaction.